Uganda's Remittance Corridors from United Kingdom, United States, and South Africa : Challenges to Linking Remittances to the Use of Formal Services - Endo, Isaku; Namaaji, Jane; Kulathunga, Anoma (World Bank, 2012)
The purpose of this study is to gather a broad spectrum of remittance data related to Uganda and the three remittance corridors and compile such information in a comprehensive report with a view to sharing knowledge and expertise. In addition to knowledge sharing, it is expected that the information and findings in this report will assist the authorities in developing the Ugandan remittance market and mitigating related risks. Being the first Bilateral Remittance Corridor Analysis (BRCA) report to be conducted with the partnership of a local authority adds to the significance of the endeavor. This report comprises five chapters with supporting annexes. The first chapter is a introductory chapter continues with data showing remittance trends from a global perspective and in Sub-Saharan Africa and their comparison with those of Uganda. Chapter two analyzes and compares the three remittance-sending countries in terms of remittance flows, remittance mechanisms and related costs, and regulations. Chapter three focuses onUganda as a remittance-receiving country, describing the remittance flows, market players, distribution network, access. Chapter four summarizes the main findings and observations. This report presents policy recommendations for Uganda as well as for remittance-sending countries in the final chapter.